2019
DOI: 10.1002/2050-7038.2836
|View full text |Cite
|
Sign up to set email alerts
|

A new digital control of four‐leg inverters in the natural reference frame for renewable energy–based distributed generation

Abstract: Summary Nowadays, stand‐alone dispersed generation (DG) supplied from renewable energies is rapidly growing. In such a condition, four‐leg inverter can be considered as a successful option to supply unbalanced loads, especially in transformerless systems. In this paper, four‐leg inverter is modeled considering the fourth line inductor. The neutral (fourth) line inductor causes a high coupling through control variables in the natural reference frame. To avoid several transformations among reference frames, a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Boost converter is a step‐up chopper that provides larger output voltage compared to its input voltage. From prior work, 6‐28 it is observed that several types of linear, nonlinear, optimized, and advanced control approaches are already applied in Boost converters.…”
Section: Boost Convertermentioning
confidence: 99%
See 2 more Smart Citations
“…Boost converter is a step‐up chopper that provides larger output voltage compared to its input voltage. From prior work, 6‐28 it is observed that several types of linear, nonlinear, optimized, and advanced control approaches are already applied in Boost converters.…”
Section: Boost Convertermentioning
confidence: 99%
“…Modeling and advanced control architectures of switching converters which having nonminimum phase problem have been reported by Banerjee et al, Ling et al, Rana et al [20][21][22][23] Robust voltage control with wide parametric variations of switching converters for renewable energy applications are reported in prior works. 24,25 The comparison between different classical and advanced control methods like IMC, SMC for a Boost converter are discussed in Ghosh and Banerjee. 1 Advanced robustness studies, adaptive sliding mode based control and nonlinear dynamics analysis by varying different control parameters in switching converters are reported in recent literatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an unbalanced loading condition is an inevitable situation that occurs frequently in standalone applications. As a result, a fourth wire power system is mandatory to supply any unbalanced loads …”
Section: Introductionmentioning
confidence: 99%
“…The existing literature presents different control strategies [1924] to control both islanded single‐ and three‐phase inverters. These strategies include the interconnection and damping assignment passivity‐based controller (IDA‐PBC) [19], model predictive control (MPC) [20], Hnormal∞ three degrees of freedom (Hnormal∞‐3DOF) controller [21], deadbeat controller [22], modified linear active disturbance rejection control (MLADRC) [23], and unbalanced synchronous reference frame (USRF) controller [24]. These controllers are robust against uncertainties and have lower THDs while meeting the standard requirements.…”
Section: Introductionmentioning
confidence: 99%